The Industrial Mobility of Displaced Workers - Fallick, Bruce Chelimsky (Journal of Labor Economics, 1993)
This article uses a two-industry model of unemployment duration and job search to estimate rates of transition of displaced workers from unemployment to employment, distinguishing between employment in a worker's previous industry and in other industries. The competing-risks model allows inferences about search strategies to be drawn from data concerning employment outcomes and allows tests of some fundamental implications of search theory. There is evidence that improvements in the prospects for employment in their previous industry induce displaced workers to reduce search intensity or increase reservation wages in other industries.